N1-Methylnicotinamide Improves Hepatic Insulin Sensitivity via Activation of SIRT1 and Inhibition of FOXO1 Acetylation - Jingfan Zhang; Yu Chen; Cong Liu; Ling Li; Ping Li (Journal of Diabetes Research)
Objective. To explore the effects of N1-methylnicotinamide (MNAM) on insulin resistance and glucose metabolism in obese type 2 diabetes mellitus (T2DM) mice and regulatory mechanisms of the NAD-dependent deacetylase sirtuin-1 (SIRT1)/forkhead box protein O1 (FOXO1) pathway. Methods. Blood glucose and insulin levels were examined in mice. HE and oil red O staining were used to observe the effects of MNAM on liver lipid deposition in ob/ob mice. Real-time PCR and Western blotting were used to detect expression of gluconeogenesis, insulin signaling-related proteins, and SIRT1/FOXO1 pathway-related proteins. L-O2 cells were cultured as a model of insulin resistance, and MNAM and SIRT1 inhibitors were administered in vivo. Residual glucose and insulin signaling-related proteins were detected and the mechanisms associated with the SIRT1/FOXO1 signaling pathway in insulin resistance explored. Results. MNAM can effectively reduce levels of fasting blood glucose and insulin, improve liver morphology, and reduce lipid accumulation in obese type 2 diabetes mellitus mice. MNAM also downregulates the key proteins in the gluconeogenesis pathway in the liver, upregulates Sirt1 expression, and reduces acetylation of the FOXO1 protein. In vitro, MNAM could promote the glucose uptake capacity of L-O2 cells induced by palmitic acid (PA), a saturated fatty acid that induces IR in various scenarios, including hepatocytes, improving insulin resistance. As Sirt1 expression was inhibited, the reduction of hepatocyte gluconeogenesis and the regulation of the insulin signaling pathway by MNAM were reversed. Conclusion. MNAM activates SIRT1 and inhibits acetylation of FOXO1, which in turn regulates insulin sensitivity in type 2 diabetic mice, leading to a reduction of hepatic glucose output and improvement of insulin resistance.